Risk factors associated to diabetic foot at Luis N. Saenz PNP hospital, year 2017: Factores de riesgo asociados a pie diabético en el hospital PNP Luis N. Saenz, año 2017 - Arribasplata Espinoza, Yajaira (2019)
Introduction: Diabetic foot is one of the most serious and frequent complications of diabetes mellitus, for this reason it is important to know the risk factors that trigger it. Objective: To determine the risk factors associated with diabetic foot in the PNP Luis N. Sáenz Hospital, 2017. Methods: Observational, retrospective, analytical, case and control study of 165 patients (55 cases and 110 controls) treated in the endocrinology service in 2017. Modifiable and non-modifiable risk factors associated with the development of diabetic foot were studied; the information of the clinical histories was collected through a data collection form, which was analyzed by means of the SPSS program version 25.0 using the statistical models of Chi square and the odds ratios with a level of significance less than 0.05% and a range of 95% confidence. Results: The risk factors associated with diabetic foot are disease time (p: 0.000, OR: 12.77, CI: 4.12 - 39.60); poorly controlled glycosylated hemoglobin (p: 0.029, OR: 4.55, CI: 1.17 - 17.68); Onychomycosis (p: 0.014, OR: 7.10, CI: 1.48 - 34.07); antecedent of smoking (p: 0.031, OR: 2.66, CI: 1.09 - 6.34) and chronic kidney disease (p: 0.047, OR: 3.023, CI: 1.01 - 9.0). Conclusion: We conclude that there is a statistically significant association between time of illness, poorly controlled glycosylated hemoglobin, onychomycosis, chronic kidney disease, history of smoking and developing diabetic foot. DOI:10.25176/RFMH.v19.n2.2070